2017
DOI: 10.3324/haematol.2017.168674
|View full text |Cite
|
Sign up to set email alerts
|

Notch2 blockade enhances hematopoietic stem cell mobilization and homing

Abstract: Despite use of newer approaches, some patients being considered for autologous hematopoietic cell transplantation (HCT) may only mobilize limited numbers of hematopoietic progenitor cells (HPCs) into blood, precluding use of the procedure, or being placed at increased risk of complications due to slow hematopoietic reconstitution. Developing more efficacious HPC mobilization regimens and strategies may enhance the mobilization process and improve patient outcome. Although Notch signaling is not essential for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
1
15
0
2
Order By: Relevance
“…This is sustained through an auto-regulatory loop that is dynamically regulated from cell surface to intracellular stores ( Lapidot and Kollet, 2002 ). CXCR4 is regulated by BM factors, some of which include hypoxia ( Scheurer et al., 2004 ), Notch ( Wang et al., 2017 ), glucocorticoid ( Guo et al., 2017 ), and prostaglandin E 2 (PGE 2 ) ( Goessling et al., 2011 ) signaling pathways. However, the functional capacity of hPSC-HPCs to respond to BM regulatory cues remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This is sustained through an auto-regulatory loop that is dynamically regulated from cell surface to intracellular stores ( Lapidot and Kollet, 2002 ). CXCR4 is regulated by BM factors, some of which include hypoxia ( Scheurer et al., 2004 ), Notch ( Wang et al., 2017 ), glucocorticoid ( Guo et al., 2017 ), and prostaglandin E 2 (PGE 2 ) ( Goessling et al., 2011 ) signaling pathways. However, the functional capacity of hPSC-HPCs to respond to BM regulatory cues remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of Notch1 alone, or Notch1 and Notch2 together was found to increase the differentiation of lymphoid HSCs ( Bigas and Espinosa, 2012 ). Wang et al (2017) found that Notch 2, but not Notch 1, blockade leads to HSC mobilization. Interestingly, Notch 2 blocked, but not Notch 2 deficient, HSCs exhibited a competitive repopulating advantage and enhanced hematopoietic reconstitution.…”
Section: Important Adhesion Molecules Involved In Hsc Adhesionmentioning
confidence: 99%
“…We found that in mice receiving Notch2-blocking antibodies, but not Notch1-blocking antibodies, spleen-residing LSKs and LKs increased three- to four-fold. When mice were given G-CSF and plerixafor following four doses of anti-Notch2 treatment, a 2.5-fold increase of white blood cells, a 3- and 3.3-fold increase of LSKs and LKs were seen in the periphery, and a 3.6- and 2-fold increase of spleen-residing LSKs and LKs were found in mice receiving anti-Notch2 compared to control-treated mice 116 . However, Notch2 blockade, combined with G-CSF or plerixafor, did not affect marrow HSPC homeostasis.…”
Section: Introductionmentioning
confidence: 99%